PANORAMIC RADIOGRAPHY AND CONE-BEAM COMPUTED TOMOGRAPHY TO MEASURE DISTANCES BETWEEN ROOT APEXES AND ANATOMICAL STRUCTURES - Ferrari, Carlos Henrique [UNESP] (2022)
Aim: To compare the accuracy of the panoramic radiography with cone-beam computed tomography (CBCT) scans in measuring the distances between root apexes and the adjacent anatomical structures including the maxillary sinus and the mandibular canal. Material and Methods: A total of 200 CBCT scans (100 maxillary and 100 mandibular) from patients who also had corresponding panoramic radiography were selected. Linear measurements (in mm) presenting centralized image were made between the apexes of the maxillary teeth and the inferior wall of the maxillary sinus, and between the apexes of the mandibular teeth and the superior border of the mandibular canal by using specific software for panoramic radiography and the measurements on the coronal sections in CBCT scans. Data were submitted to inferential statistical analysis and Student’s t-test for comparison between measurements. Results: CBCT scans were significantly more accurate than panoramic radiography to measure the distances between the apexes of the maxillary teeth and the inferior wall of the maxillary sinus (p<0.05) and between the apexes of the mandibular teeth and the superior border of the mandibular canal or mental foramen (p<0.05). Conclusion: CBCT scans present more accurate measurements than panoramic radiography.